A objetividade do conhecimento e a deposição do sujeito na epistemologia de Popper - RABELO, Wallace Andrew Lopes (Universidade Federal do Pará, 2019)
The aim of this work is to investigate how objective knowledge is possible for Popper and to elucidate why the subject does not play a relevant role in the process of knowing. Popperian conception moves away from the epistemological tradition that values the subject in the process of knowing, understood by the philosopher as subjectivist view, compared with his objectivist view. In this sense, we intend to demonstrate that his conception of objective knowledge is based on a theory of three worlds, which is fundamental for the comprehension of it, since it’s precisely in world three that the products of subject reside, thus where objective knowledge is. We will show that this third world is linguistic, highlighting the importance of language for knowledge to become objective. Another aspect we intend to analyze is scientific objectivity, since Popper, besides objective knowledge in general, talks on his works about a more specific dimension related to science. We intend to clarify the logical-empirical and social conditions that allowed the debate and criticism of produced theories and, consequently, scientific objectivity. Lastly, we will present criticism of Thomas Kuhn to Popperian conception of objectivity. Since the philosopher does not make a direct critique to the way Popper conceives it, we will highlight his objections to Popper’s falsificationism and his considerations about subjective factors that influence the process of choosing theories, thus, risking the possibility of scientific objectivity.